PROBLEMATIKA YURIDIS RANGKAP JABATAN APARATUR SIPIL NEGARA DENGAN PENGURUS BADAN USAHA MILIK NEGARA: Juridicial Review Problems of Concurrent Positions of State Civil Apparatus with Management of State-Owned Enterprises - Rizkyta, Altrifi; Nasef, Muhammad Imam (AMICUS CURIAE, 2025)
The State Civil Apparatus is one of the implementing components of government which is also included as public service officials. In this case, of couse state civil service has an important role in implementing good governance in order to achieve community welfare. However, in practice the implementation of good governance is hampered by one issue, namely interlocking directorates. Interlocking directorates that occur are closely related to the ambiguity in the regulation of dual positions for state civil service and state owned enterprises administrators in statutory regulations. This research uses a normative juridicial research type, this research is descriptive in nature, the data in this research uses secondary data through literature study. Secondary data was analyzed qualitatively and conclusions were drawn using deductive methods. In this case, there are many laws and regulations related to state civil service, state owned enterprises and other decisions related to holding multiple positions that prohibit holding multiple positions, but in the state civil service law itself, it is not stated clearly about positions and consequences of hlding multiple positions which the results in holding multiple positions by several parties and as one of the reasons deemed valid for the dual posistions treatment.